School Management Based on the Philosophy of Sufficiency Economy for Sustainable Education Quality Development: School Management Based on the Philosophy of Sufficiency Economy for Sustainable Education Quality Development - Bunrottaochalee, Somawadi; Kamjit, Saowanee; Singmart, Sanook (RATANABUTH JOURNAL, 2026)
This article aims to present the concepts, principles, and practical approaches to school administration based on the Sufficiency Economy Philosophy (SEP). The focus is on applying these principles across the four major areas of school administration academic administration, budget administration, personnel management, and general administration. The core principles of the Sufficiency Economy Philosophy include moderation, reasonableness, and self-immunity, grounded in the conditions of knowledge and morality. The article concludes that school administration based on the Sufficiency Economy Philosophy strengthens organizational capacity, promotes financial discipline, enhances internal and external collaboration, and reduces educational inequality, leading to stable and sustainable development.